Performance Evaluation of Diffuser Dampers in HVAC Systems Using Volume-Weighted Average Analysis - Busu, Nur’Amirah; Mat Isa, Norasikin; Hussein, Mohamed; Hariri, Azian; Adebayo, David Shina; M.F. Abdul Ghani, (International Journal of Integrated Engineering, 2026)
Air distribution in HVAC systems plays a critical role in ensuring indoor thermal comfort and energy efficiency, yet the impact of diffuser damper design on airflow and temperature regulation is often overlooked. This study investigates the performance of three diffuser damper designs, Iris, Butterfly, and Radial under varying opening conditions, addressing the need for precise airflow control and optimized thermal distribution in indoor environments. CFD simulations were conducted using ANSYS Fluent, employing a realizable k–ε turbulence model to evaluate flow and thermal characteristics. Six key parameters; static temperature, velocity magnitude, static pressure, turbulent kinetic energy, turbulent intensity, and turbulent dissipation rate; were analysed using volume-weighted averages across the computational domain to provide a comprehensive performance assessment. Results indicated that the Iris damper consistently achieved precise temperature regulation, lower turbulence, and smoother airflow across all opening conditions, making it ideal for applications requiring stable thermal comfort and energy efficiency. The Butterfly design offered balanced performance suitable for general comfort applications, while the Radial design, despite achieving high airflow velocities, generated elevated turbulence at restricted openings, limiting its suitability for precision-controlled environments. In conclusion, the Iris damper emerged as the optimal configuration for enhancing indoor thermal comfort and optimizing HVAC system performance across diverse operational scenarios.